Problemer omkring beskrivelsen af modusbrugen i tysk "indirekte tale" - Poulsen, Sven-Olaf (HERMES - Journal of Language and Communication in Business, 1988)
A review of present Danish and German studies of modality in German indirect speech suggests they should be based on sufficiently large text corpora representing the most important text types. Productive grammars intended for interpreters should focus on texts relevant to language training and should incorporate pragmatic aspects when necessary. Reference is made to an exemplary investigation of modality and tense in indirect speech in Danish and German in judgements passed in first instance courts. Comparative analyses for each text type and language pair are needed.